Analgesic efficacy, safety, and tolerability of a long-acting abuse-deterrent formulation of oxycodone for moderate-to-severe chronic low back pain in subjects successfully switched from immediaterelease oxycodone - Markman, John; Meske, Diana S; Kopecky, Ernest A; Vaughn, Ben; O'Connor, Melinda L; Passik, Steven D (Journal of pain research, 2018)
Objectives: This post hoc analysis of data from a randomized, double-blind, placebo-controlled, enriched-enrollment randomized-withdrawal Phase III study evaluated the safety, tolerability, and analgesic efficacy of Oxycodone DETERx extended-release (ER), abuse-deterrent capsules (Xtampza[R] ER) in subjects with chronic low back pain who were successfully transitioned from immediate-release (IR) oxycodone. Methods: Continuous outcomes were analyzed using a mixed-model repeated-measures approach; binomial outcomes were analyzed using chi-squared; and time-to-event outcomes using Kaplan-Meier analyses. Results: A total of 110 subjects previously prescribed IR oxycodone entered the Open-label Titration Phase. Forty-four subjects were randomized to Oxycodone DETERx (n=22) or placebo (n=22) in the 12-week Double-blind Maintenance Phase. Efficacy results in this subgroup showed a statistically significant difference between Oxycodone DETERx and placebo in average pain intensity scores from Randomization Baseline to Week 12 (least squares mean [[+ or -] standard error], -1.88 [0.70]; P=0.0078). Additional efficacy results indicated that Oxycodone DETERx vs placebo was associated with a statistically significant benefit in durability of effect from Week 2 through Week 12 (P<0.01), numbers of subjects with a [greater than or equal to]30% (n [%] 10 [45.5%] vs 0 [0%]; P=0.0004) and [greater than or equal to]50% (10 [45.5%] vs 0 [0%]; P=0.0004) improvement in pain intensity, longer time-to-exit (P=0.0014), a greater number of subjects who completed the study (14 [63.6%] vs 4 [18.2%]), and less rescue medication use (acetaminophen; mean [SD], 163.5 [337.8] mg) vs 216.2 [377.3] mg). Adverse event profiles were consistent with opioid class effects and results from the original study; Oxycodone DETERx was well tolerated in subjects previously treated with short-acting oxycodone. Conclusions: Oxycodone DETERx resulted in clinically meaningful and statistically significant efficacy in subjects with chronic low back pain who were previously prescribed IR oxycodone and were successfully switched to ER Oxycodone DETERx. Keywords: oxycodone, DETERx, Xtampza ER, chronic low back pain, extended-release, immediate-release, opioid